If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2w + 7) * w + -99 = 0 Reorder the terms: (7 + 2w) * w + -99 = 0 Reorder the terms for easier multiplication: w(7 + 2w) + -99 = 0 (7 * w + 2w * w) + -99 = 0 (7w + 2w2) + -99 = 0 Reorder the terms: -99 + 7w + 2w2 = 0 Solving -99 + 7w + 2w2 = 0 Solving for variable 'w'. Factor a trinomial. (-9 + -1w)(11 + -2w) = 0Subproblem 1
Set the factor '(-9 + -1w)' equal to zero and attempt to solve: Simplifying -9 + -1w = 0 Solving -9 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -1w = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -1w = 0 + 9 -1w = 0 + 9 Combine like terms: 0 + 9 = 9 -1w = 9 Divide each side by '-1'. w = -9 Simplifying w = -9Subproblem 2
Set the factor '(11 + -2w)' equal to zero and attempt to solve: Simplifying 11 + -2w = 0 Solving 11 + -2w = 0 Move all terms containing w to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -2w = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -2w = 0 + -11 -2w = 0 + -11 Combine like terms: 0 + -11 = -11 -2w = -11 Divide each side by '-2'. w = 5.5 Simplifying w = 5.5Solution
w = {-9, 5.5}
| 10+2x=26 | | 3(x-8)=4(3x+2)-5 | | 6(3x-5)-7x=22 | | 8x^3+28x^2+20x=0 | | 1+(-a/9)-4=0 | | 0.4x+0.2=-1 | | x^10=30 | | y=-3(1)+5 | | .25(8y-4)=x | | 7(x-2)=7x-14 | | a^4-a^2-6=0 | | 7x-(5x-2)=-8 | | -25n^2+57n=-14 | | 6x+8.74=4x+11 | | (2w+5)w-42=0 | | 18=-32w+20 | | y=-3(0)+5 | | 5,-2= | | 2-y=5wz+15 | | 8-m+3m=16 | | 7(x+2)=-56 | | -0.9p+-3=0.6 | | -3-7x=-24 | | -3x+2=7x-8 | | (5,-2)m= | | 4x^2+7x-10=0 | | 5/-2= | | 4-5x=-41 | | -0.9+-3=0.6 | | 3x-7=5x-25 | | -10/3=y/6 | | y^3-16y=0 |